Are Polymer-Based Smart Materials Unlocking the Path to Sustainable Manufacturing for a Net-Zero Economy? Current Trends and Potential Applications - Karishma M. Qureshi; Alok Yadav; Rajiv Kumar Garg; Anish Sachdeva; Amal Abdulrahman; Saleh Yahya Alghamdi; Mohamed Rafik Noor Mohamed Qureshi (IEEE Access)
The drive toward a net-zero economy (NZE) has pressured the manufacturing sector to adopt sustainable practices to minimize negative environmental impacts while ensuring resource efficiency. In this context, polymer-based smart materials have emerged as a promising solution, offering unique properties that respond to external stimuli, enabling more adaptive and efficient manufacturing processes. These materials not only reduce waste and energy consumption but also enhance product lifespans through innovations such as self-healing, recyclability, and degradation control (techniques to manage the breakdown of materials for extended usability and reduced waste). Despite the growing interest, combining polymer-based smart materials into manufacturing processes to achieve sustainability is still underexplored. Limited studies have comprehensively reviewed their potential in supporting sustainable manufacturing, especially in the context of net-zero emissions. This study aims to fill this gap by employing a systematic literature review (SLR) and bibliometric analysis to enhance advancements and challenges in polymer-based smart materials for sustainable manufacturing (SM). This study examines how these materials reduce energy consumption, waste, and environmental impact across various manufacturing sectors through a comprehensive analysis of current advancements, challenges, and industrial applications. The outcomes provide actionable insights for researchers and industry practitioners to accelerate the integration of smart materials into SM processes. This study identifies key factors and future research directions, offering insights for industry practitioners and researchers on the role of these materials in achieving a NZE.